The Effects of Neuromuscular Electrical Stimulation on Pharyngeal Transit Time - Kim, Seon-Rye; Kwon, Ki-Hyun; Cho, Byung-Jun (Journal of Physical Therapy Science, 2013)
[Purpose] The purpose of this study was to identify the effects of Neuromuscular Electrical Stimulation (NMES) on pharyngeal transit time. [Subjects] Subjects were divided into normal old persons aged over 70 (N=18), and normal young persons aged under 30 (N=10). [Method] We measured the Pharyngeal Transit Time (PTT) to determine their swallowing characteristics. NMES was used to stimulate old group’s suprahyoid and infrahyoid muscles 60 minutes a day, 5 days a week for 2 weeks using four electrodes. We used SPSS version 14.0 to analyze and compare the data between the 2 groups. [Results] After NMES, PTT of the normal old group became significantly shorter. PTT was much shorter, but was still longer than that of the normal young group. [Conclusion] The PTTs of the two groups classified by age were significantly different.